Ignorance in organisations : a systematic literature review - Jalonen, Harri (Springer, 2023)
This study is linked to previous research that approaches organisations as systems of shared meaning where ignorance is created and sustained, either unintentionally or deliberately, through various social interactions,symbolic processes, and organisational structures. While previous studies have touched upon organisational ignorance, there is a lack of systematically conducted research on its many forms and its many sources. This study analyses the causes, characteristics, and consequences of organisational ignorance. By reporting a systematic review of the literature, the paper contributes to the theory of organizational ignorance by developing a framework of organisational ignorance comprising the manageability (intentional or unintentional) and dynamics (bounded or expanding) of ignorance. Instead of framing ignorance as something that should be avoided, the study adopts anuanced approach to the organisation of ignorance.
Keywords: organisational ignorance; systematic review; knowledge management; ignorance; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|